2020
DOI: 10.31234/osf.io/exmqt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event-related potentials, inhibition and Alzheimer's disease risk in cognitively intact elders

Abstract: Despite advances in understanding Alzheimer’s disease (AD), prediction of AD prior to symptom onset remains severely limited, even when primary risk factors such as the apolipoprotein-E (APOE) ε4 allele are known. Although executive dysfunction is highly prevalent and is a primary contributor to loss of independence in those with AD, few studies have examined neural differences underlying executive functioning as an indicator of risk for AD prior to symptom onset, when intervention might be effective. This stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…However, this conclusion is tentative, as a majority of these studies employed an oddball paradigm (49%), whilst the few studies that did report significant differences in N200 amplitude between AD patients and controls utilised more complex tests of attention than the oddball task, such as the Erickson Flanker Task (Wang et al, 2013) attentionally cued discrimination task (Lockwood et al, 2018), and go/no-go tasks, (Crawford, 2015). This indicates that oddball paradigms may not be complex enough to demonstrate differences in N200 amplitude, a result supported by Elverman et al, (2021), who observed that as attentional task complexity increased, differences between older adults carrying the E4 apolipoprotein allele, a risk factor for AD, became more distinguishable. Studies indicating differences in N200 latency between AD and controls also present mixed results, however most studies do present significantly prolonged N200 latencies in AD patients (see Howe, 2014).…”
Section: Erp Studies -Attention Span In Admentioning
confidence: 99%
See 1 more Smart Citation
“…However, this conclusion is tentative, as a majority of these studies employed an oddball paradigm (49%), whilst the few studies that did report significant differences in N200 amplitude between AD patients and controls utilised more complex tests of attention than the oddball task, such as the Erickson Flanker Task (Wang et al, 2013) attentionally cued discrimination task (Lockwood et al, 2018), and go/no-go tasks, (Crawford, 2015). This indicates that oddball paradigms may not be complex enough to demonstrate differences in N200 amplitude, a result supported by Elverman et al, (2021), who observed that as attentional task complexity increased, differences between older adults carrying the E4 apolipoprotein allele, a risk factor for AD, became more distinguishable. Studies indicating differences in N200 latency between AD and controls also present mixed results, however most studies do present significantly prolonged N200 latencies in AD patients (see Howe, 2014).…”
Section: Erp Studies -Attention Span In Admentioning
confidence: 99%
“…As poor impulse control has been noted as a potential symptom of AD (Mendez & Shapira, 2013), it may indicate why AD patients elicit lower N200 amplitudes than controls in tests like the go/no go, as they have less cognitive resources available to allocate to impulse control. This theory is contentious however, particularly as a study by Elverman et al, (2021) showed that participants with the ɛ4+ Apolipoprotein E gene, a primary risk factor in AD development, showed higher peak amplitudes as part of a no/go task than controls.…”
Section: Erp Datamentioning
confidence: 99%